Diethyl sinapate-grafted cellulose nanocrystals as nature-inspired UV filters in cosmetic formulations. (September 2021) - Mendoza, D.J.; Maliha, M.; Raghuwanshi, V.S.; Browne, C.; Mouterde, L.M.M.; Simon, G.P.; Allais, F.; Garnier, G.
Abstract: Inspired by nature's photoprotection mechanisms, we report an effective UV-blocking nanomaterial based on diethyl sinapate-grafted cellulose nanocrystals (CNC-DES). The colloidal stability and UV-blocking performance of CNC-DES in aqueous glycerol (a common humectant in petroleum-free cosmetic formulations) and in a commercially available moisturizing cream were studied. Grafting the water-insoluble DES onto CNCs renders it dispersible in these water-based formulations, thanks to the excellent water-dispersibility of CNC nanoparticles. Glycerol dispersions containing 0.1 to 1.5 wt% CNC-DES display very high UV-blocking activity owing to the anti-UV DES moieties anchored onto CNCs. A facial cream blended with 1.5 wt% CNC-DES exhibits an SPF of 5.03, which is higher than a commercially available sunscreen with the same active ingredient concentration (SPF = 3.84). DPPH radical scavenging assay also showed the antioxidant potential of CNC-DES, albeit coinciding with a significant reduction in antioxidant activity after grafting DES onto CNCs. Cytotoxicity measurements revealed the CNC-DES not to cause significant cytotoxicity to murine fibroblast cells after 24 h of exposure. Overall, CNC-DES exhibits strong anti-UV and antioxidant properties and is water-dispersible, biocompatible, non-greasy, and lightweight. This study demonstrates the exceptional potential of DES-grafted CNCs as nature-inspired UV filters in the next generation of cosmetic formulations, including those for sensitive skins. Graphical abstract: In this work, diethyl sinapate-grafted CNCs (CNC-DES) was explored as potential UV filters in cosmetic formulations. Grafting the water-insoluble DES onto the water-dispersible CNCs increases its dispersibility in aqueous glycerol and a commercially available oil-free moisturizing cream. CNC-DES exhibits strong anti-UV and antioxidant properties and is water-dispersible, biocompatible, non-greasy, and lightweight. Image 1